HUBUNGAN ANTARA KECERDASAN EMOSIONAL DENGAN MOTIVASI BELAJAR SISWA KELAS XI DI SMA NEGERI 1 MUARO JAMBI - Suryati, Suryati; Gutji, Nelyahardi; Rahmayanty, Dinny (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2024)
This research is motivated by problems releted to student learning motivation in schools which are influenced by several factors one of which is emotional intelligence. Motivation plays an important role in improving student learning outcomes, if students’ emotional intelligence is low it can cause students’ learning motivation to be low, resulting is various problem such as liking to look at other people’s assignments, chatting daring class huors, leaving class and not following process until the end. The research uses a quatitative approach with correlation research methods, while for sampling technique, the number of samples used in this research was 122 class XI student at SMA Negeri 1 Muaro Jambi. The instrument used was a questionnaire with the a Likert scale. The results of the research show a significant value of 0,000 ≤ 0,05 and the calculated r value of 0,660 is in range (0,41-0,70) which is interpreted as being in the category of having a moderate relationship (adequate relatioship) so it can be cancluded that there is a positive relationship. And significant relationship between emtional intelligence and learning motivation of class XI SMA Negeri 1 Muaro Jambi.